The Relationship Between Game Online Addiction and The Tendency for Verbal Agressiveness in Multiplayer Online Battle Arena - Nur Indah Komala Sari; Muh. Nur Hidayat Nurdin; Tri Sulastri (ARRUS Journal of Social Sciences and Humanities, 2023)
Playing online games is an activity that is popular with various groups, not only children or adolescents, playing online games is also widely practiced by early adults to the elderly. Verbal aggression occurs due to online game addiction, so self-control is needed for Multiplayer Online Battle Arena (MOBA) users. This game emphasizes the cooperative nature of each player, the players will choose and control one game character that is mastered, and will form a strategy for the team which is a strong unit of various abilities and advantages that are unique and different from each character. in the game being played. This study aims to determine the relationship between online game addiction and verbal aggressive tendencies in Multiplayer Online Battle Arena (MOBA) players. The research method used is quantitative research methods. The subjects in this study were men and women aged 18-25 years, who were obtained using a nonprobability sampling technique with the accidental sampling method. The research data was tested using the Cronbach's alpha reliability test using the SPSS 23.0 application. The measuring tools used in this research are online game addiction scale and verbal aggressiveness scale. The results showed that there was a positive relationship between addiction to online games of the Multiplayer Online Battle Arena (MOBA) type and the tendency for verbal aggressive behavior was 0.709 (p <0.000) meaning that there was a significant positive relationship between online game addiction for moba and verbal aggressive behavior.